3Shape Digital Design Software in Splints Creation—A Pilot Study - Shopova, Dobromira; Yordanova, Miroslava; Yordanova, Svetlana (European Journal of Dentistry, 2021)
Objectives Digital technologies have widened their horizons into the world of dental medicine and now further expanding to cover all branches. This new modern technology replaces traditional laboratory techniques allowing effective patient care. Patients who suffer from bruxism—the act of involuntary habitual grinding of teeth—have widely been benefited by splint treatments. The aim of this article is to display the variety of occlusal splints that can be created by the 3Shape Digital Design Software and their application in specific clinical situations.Materials and Methods Six variations in the splints were created digitally—three with uncombined designs and the remaining three with a combination of two of the main options available. During this study, 36 splints were made for patients aged 24 to 55 inclusively.Results The largest number of splints according to the clinical picture were made of “raise to antagonist cusp tips” (14 pieces) and the remaining were of combined type “raise to antagonist cusp tips + raise to antagonist plane” (12 pieces). There thickness was within the range of 1.5 and 5 mm.Conclusion 3Shape Digital Design Software—Splint Studio is a suitable system for designing and creating occlusal splints with respect to certain clinical situations. It is possible to combine the three main types in a separate section of the dental arch according to the case.
Keywords: occlusal splints; bruxism; digital technologies; 3Shape